Queering the Shakespeare Film Gender Trouble, Gay Spectatorship and Male Homoeroticism - Patricia, Anthony Guy (Bloomsbury Academic, 2017)
A range of mainstream and independent English language film productions of A Midsummer Night's Dream, Romeo and Juliet, Othello, Twelfth Night, and The Merchant of Venice take centre stage in Queering the Shakespeare Film. This study critiques the various representations of the queer - broadly understood as that which is at odds with what has been deemed to be the normal, the legitimate, and the dominant, particularly - but not exclusively - as regards sexual matters, in the Shakespeare film. The movies chosen for analysis correspond deliberately with those Shakespeare plays that, as written texts, have been subjected to a great deal of productive study in a queer context since the beginnings of queer theory in the early 1990s. Thus the book extends the ongoing queer discussion of these written texts to their counterpart cinematic texts. Queering the Shakespeare Film is a much-needed alternative and complementary critical history of the Shakespeare film genre.